Motivasi Kerja dan Kinerja Karyawan: Peran Komitmen Organisasi pada Industri Perkapalan di Surabaya - Isti’anah, Putri Rahmatul; Fatoni, Fandi; Anggela, Anggra Olivia (Seminar Nasional Manajemen, 2025)
The rapid expansion of the Indonesian economy has intensified competition, compelling companies to seek sustainable strategies for achieving competitive advantage. Human resource optimization, particularly through improved employee performance, has become a critical factor in organizational success. In this context, leadership plays a pivotal role in fostering motivation and commitment among employees to enhance overall organizational performance. This study examines the effect of work motivation on employee performance, with organizational commitment as a mediating variable. Data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. The findings are expected to contribute to a deeper understanding of how motivation and commitment interact to drive employee performance, offering both theoretical insights and practical implications for organizational development.